Corrosion Zones of Rebar in High-Volume Fly-Ash Concrete through Potentiodynamic Study in Concrete Powder Solution Extracts: A Sustainable Construction Approach - Manish Kumar; Jitu Kujur; Rajeshwari Chatterjee; Somnath Chattopadhyaya; Shubham Sharma; Shashi Prakash Dwivedi; Ambuj Saxena; S. Rajkumar; Ashutosh Anand (Advances in Civil Engineering)
This research reports the experimental outcomes of potentiodynamic analysis of the steel reinforcement in carbonated and uncarbonated high-volume fly-ash concrete powder solution extracts (CPSE). Different percentages of fly-ash content have been used to form a high-volume fly-ash concrete (0%, 20%, 40%, 50%, 60%, and 70%) with three different types of steel reinforced. Three different water-to-binder ratios (0.35, 0.40, and 0.45) have been used to form the reinforced concrete. The different zones of corrosion were observed through the anodic polarization curve, which was obtained through the potentiodynamic linear sweep test. It has indeed been demonstrated that concrete with up to 50% fly ash shows better resistance against carbonation, as compared to Ordinary Portland Cement (OPC) concrete. Fully active anodic polarization curve is obtained for carbonated concrete. Corrosion-resistant steel performed better as compared to TATA TMT and SISCON TMT types of steel. The ANOVA also verifies the experimental observation, which shows that the content of fly ash and types of steel decide the extent of corrosion in the concrete. It has also been observed that the interaction between the fly-ash content and water-binder proportion and also the interaction between fly ash and the type of steel show the strong effect on the corrosion activity, which decides the extent of different zones of corrosion.